2016
DOI: 10.1163/22134808-00002509
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Correspondences in Non-human Mammal Communication

Abstract: For both humans and other animals, the ability to combine information obtained through different senses is fundamental to the perception of the environment. It is well established that humans form systematic cross-modal correspondences between stimulus features that can facilitate the accurate combination of sensory percepts. However, the evolutionary origins of the perceptual and cognitive mechanisms involved in these cross-modal associations remain surprisingly under-explored. In this review we outline recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 184 publications
(163 reference statements)
0
22
0
Order By: Relevance
“…For example, studies have shown that signal receivers direct attention in a spatially appropriate manner in response to certain types of alarm calls, such as directing visual attention upwards in response to alarm signals specific to aerial predators [ 61 , 62 ]. Other research has shown, more generally, the tendency of multiple species to orient visual attention based partly on simple signal characteristics such as frequency [ 63 ]. Collision mitigation approaches could co-opt such natural tendencies in the behaviors of at-risk birds, to help elicit collision avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that signal receivers direct attention in a spatially appropriate manner in response to certain types of alarm calls, such as directing visual attention upwards in response to alarm signals specific to aerial predators [ 61 , 62 ]. Other research has shown, more generally, the tendency of multiple species to orient visual attention based partly on simple signal characteristics such as frequency [ 63 ]. Collision mitigation approaches could co-opt such natural tendencies in the behaviors of at-risk birds, to help elicit collision avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Promising areas of future research in bats and beyond would be how receivers accomplish cross‐modal integration of social signals (e.g. Kozak & Uetz, ; Ratcliffe, Taylor, & Reby, ) or decode temporally segregated social information in the same sensory channel (e.g. Collier, Townsend, & Manser, ; Jansen, Cant, & Manser, ).…”
Section: Discussionmentioning
confidence: 99%
“…The current limited body of the literature on cross-modal recognition can provide insights into the factors that may lead to the evolution of cross-modal recognition [38]. These species all display extended social relationships with conspecifics [9,11,13,14,18], while some of those that have been shown to have cross-modal recognition of humans have a long history of domestication, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cross-modal preferential looking paradigm (e.g. [37,38]), we first presented goats with calls of either their stablemate (individual sharing their pen at night) or another familiar herd member in an arena where they could simultaneously observe both individuals. Secondly, we presented them with calls of one of two herd members, in order to test whether goats possess cross-modal representations of other, less familiar individuals than their stablemate.…”
Section: Introductionmentioning
confidence: 99%